THE EFFECT OF FIRM SIZE AND SALES GROWTH ON FIRM VALUE: ROA AND COST EFFICIENCY AS MEDIATORS - Rizki Aisyah Maharani; Elvin Bastian; Iis Ismawati (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study addresses inconsistent evidence on whether firm size and sales growth create market value directly or only after they improve internal performance. It tests return on assets (ROA) and the BOPO operating-cost ratio as mediating pathways.Empirical Problem: During 2021-2025, the Indonesian Consumer Non-Cyclicals index declined by 61.27%, while the composite market index increased by 17.34%, indicating that defensive demand and revenue expansion did not automatically translate into market valuation.Research Methodology: A quantitative causal-explanatory design covered 37 Consumer Non-Cyclicals companies listed on the Indonesia Stock Exchange, yielding 185 firm-year observations. The thesis outputs were analyzed through three pooled company-year regressions and one-tailed Sobel tests in EViews 12.Results: Firm size was positively associated with firm value and ROA, whereas sales growth affected ROA but not firm value directly. Firm size increased the BOPO ratio, sales growth did not significantly affect BOPO, and both ROA and BOPO were positively associated with firm value. The reported one-tailed Sobel tests indicated ROA mediation for both antecedents and BOPO mediation for firm size only.Conclusions: ROA is the more consistent value-creation pathway. The positive BOPO coefficient must be interpreted as higher operating-cost intensity, not as an efficiency improvement; it may capture expansion, distribution, or capability-building expenditures that investors tolerate when accompanied by scale.Limitations: The study is limited to one sector, a five-year window, a pooled estimator without reported panel-model selection tests, an inverse BOPO proxy, and Sobel rather than bootstrap mediation evidence.Contributions: The study extends signaling theory with a sequential-confirmation mechanism: size and sales growth operate as preliminary signals, while profitability and operating-cost structure confirm or qualify their valuation relevance. Managers should evaluate expansion through incremental ROA and distinguish productive operating investment from avoidable cost inefficiency